Pedagogical Conditions for Coordination Development in Girls of Primary School Age through Rhythmic Gymnastics - С. І. Марченко; Є. Г. Захарова (OVS LLC, 2015)
The research objective is to experimentally verify the effectiveness of the use of rhythmic gymnastics means that have been systematized to develop coordination abilities in girls of primary school age. Research methods: method of theoretical analysis and generalization of literary sources, method of control studies, pedagogical experiment, methods of mathematical statistics. Research results. The coordination readiness level evaluation demonstrated that at the beginning of the pedagogical experiment the level of the majority of the second-grade girls was low (22.85%), below average (39.97%), and average (11.42%); that of the third-grade girls was below average (57.1%), average (34.26%); and that of the fourth-grade - below average (29.3%), and average (62.06%). After the pedagogical experiment the number of the second-, third- and fourth-grade girls with the low level decreased by 19%, 13.4%, 10.4% in the experimental groups and by 16.3%, 11.8%, 9.8% in the control groups respectively; the number of the girls with the below-average level decreased by 14.7%, 32.7%, 23.1% in the experimental groups and by 12.4%, 21%, 19.1% in the control groups. The positive changes in the level of coordination abilities occurred both in the control and the experimental groups, with the results improved in favor of the experimental groups.